2009
DOI: 10.1227/01.neu.0000339130.90379.89
|View full text |Cite
|
Sign up to set email alerts
|

Upper-Extremity Peripheral Nerve Injuries

Abstract: Good outcomes after median and radial nerve repairs are attributable to the following factors: the median nerve's innervation of proximal, large finger, and thumb flexors; and the radial nerve's similar innervation of proximal muscles that do not perform delicate movements. This is contrary to the ulnar nerve's major nerve supply to the distal fine intrinsic hand muscles, which require more extensive innervation. The radial nerve also has a motor fiber predominance, reducing cross-motor/sensory reinnervation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Of these, 126 were selected for review of the full text after primary screening, and 67 were judged to meet the criteria for inclusion in the present study[78910111213141516171819202122232425262728293031323334353637383940414243444546474849505152535455565758596061626364656667686970717273]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 126 were selected for review of the full text after primary screening, and 67 were judged to meet the criteria for inclusion in the present study[78910111213141516171819202122232425262728293031323334353637383940414243444546474849505152535455565758596061626364656667686970717273]. …”
Section: Resultsmentioning
confidence: 99%
“…In the present study, median and ulnar nerve sensory recovery had ORs for good to excellent sensory recovery of 0.44 and 0.36, respectively, compared with radial nerve sensory recovery; and the ulnar nerve had an OR for good to excellent motor recovery of 0.30 compared with radial nerve motor recovery. Murovic et al[68] reported that the rates of good to excellent results after the repair of radial, median, and ulnar nerve injuries were 86%, 75%, and 56%, respectively. Ruijs et al[4] reported that the rate of motor recovery was 71% lower after the repair of ulnar nerve injuries than median nerve injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proponents of the 2-stage approach argue that the extent of nerve damage and the resultant zone of injury cannot be declared at the initial stage. 8,9 During the delayed reconstruction, injured nerve tissue can be precisely identified and resected, followed by graft interposition. In the acute setting, this distinction between healthy and injured nerve is not possible, and therefore damaged nerve may be left behind, which could consequently jeopardize a satisfactory outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The most affected nerves in the upper limb are ulnar, median, radial, and digital nerves (7)(8)(9). Mild injuries may cure without intervention, however, severe injuries may lead to lifelong disabilities if they are not diagnosed and treated appropriately (2,3,10,11).…”
Section: Introductionmentioning
confidence: 99%